The The Effect of Electronic Word of Mouth Communication through Instagram on the Decision of Domestic Tourists Visiting Peucang Island - Ronny Yudhi Septa Priana (Politeknik Pariwisata Palembang, 2021)
The purpose of this research is to analyze the influence of word of mouth intensity, positive valence word of mouth, and word of mouth content partially and simultaneously to the decision of domestic tourists visiting Peucang Island tourism object in Pandeglang. The population in this study were individuals who had made tourist visits at Peucang Island at Ujung Kulon National Park in Pandeglang. This research uses non probability sampling method with purposive sampling technique, and the sample used is 120 people. The result of data analysis shows that: 1) Word of mouth intensity has a positive and significant influence on the decision of domestic tourists visiting Peucang Island in Pandeglang District; 2) Word of mouth positive valence through social media instragram has a positive and significant influence on the decision of domestic tourists visiting Peucang Island in Pandeglang; 3) Word of mouth content through social media instagram have a positive and significant influence on the decision of domestic tourists visit Peucang Island in Pandeglan; 4) Word of mouth intensity, positive valence word of mouth and word of mouth content, meaning word of mouth intensity, positive valence word of mouth and word of mouth content through social media instagram simultaneously has a positive and significant influence on the decision of domestic tourists visiting Peucang Island in Pandeglang.